The Combination Effect of Motor Relearning Program and Positive Affirmation on Functional Abilities and Quality of Life in Post Stroke Patients at Ngudi Waluyo Wlingi Hospital - Setyo Wahyudi; Yuly Peristiowati; Agusta Dian Ellina; Nurdina; Ratna Wardani (Universitas STRADA Indonesia, 2025)
Background: Stroke is a disease that causes chronic disability. It is hoped that the combination of Motor Relearning Program (MRP) and Positive Affirmation (PA) will be able to improve the functional abilities and quality of life (QoL) of post-stroke patients considering that there is no intervention that combines these two methods. Purpose: The purpose of this study was to analyze the effect of the combination of MRP and PA on the functional abilities and QoL of post-stroke patients at Ngudi Waluyo Wlingi Hospital. Methods: The research design used is quantitative research using the true experimental pre and post with controlled design. The sampling technique used was Simple Random Sampling with a sample of 7 people given a combination of MRP and PA (Group A), 7 people given MRP treatment (Group B), 6 people given PA treatment (Group C), and 7 people in the control group given conventional physiotherapy treatment (CPT) (Group D). The research was carried out for 4 weeks with 3 sessions. Functional ability was measured using Barthel Index and QoL was measured using Stroke Impact Scale. Paired sample t, ANOVA, Tukey post hoc, and Games-Howell post hoc tests was used to analyzed the data. Results: With the exception of the PA group, which had a p-value of 0.000 > 0.05 for functional ability, the results of the paired t-test showed that the p-value was 0.000 for both functional ability and QoL for all treatment groups. This suggests that functional abilities were unaffected by PA. ANOVA test results revealed a significance value of 0.000, below the 0.05 alpha threshold. This indicates that the pre-post test results for each treatment group differ significantly from those of the control group. Group C (PA) and Group A (a mix of MRP and PA) had the biggest mean difference, according to the Tukey test, with a value of 38.80. Additionally, the Games-Howell test's QoL scores showed. Conclusion: PA treatment has no effect on improving the patient's functional ability, but has an effect on patient’s QoL, so it is recommended to combine it with MRP treatment. The combination treatment of MRP and PA is recommended to be given simultaneously to improve the functional ability and QoL of post-stroke patients for maximum results.